Proses Berpikir Siswa SMP dalam Menyelesaikan Masalah Kontekstual Ditinjau dari Gaya Kognitif Reflektif-Impulsif - Risalatus Sa'idah; Endah Budi Rahaju (MATHEdunesa, 2023)
Mathematics learning should emphasize students' thinking processes so that they can reveal the processes that take place when students solve problems so that they are by the goals of learning mathematics according to Permendikbud Number 21 of 2016. The use of contextual problems can motivate students when solving problems. Contextual problems are found in algebraic materials. Each student has a different cognitive style, including reflective and impulsive cognitive styles. When students have different cognitive styles, the way to solve problems is also different, so it will trigger differences in students' thinking processes. This research is qualitative descriptive research because it fits the purpose of this study, which is to describe the thinking processes of junior high school students with reflective and impulsive cognitive styles in solving contextual problems in algebra material. The subjects of this study were two students of class VII-E at SMPN 2 Porong with different cognitive styles and high levels of mathematical ability. The instruments used in this study were cognitive style tests (Matching Familiar Figure Test), mathematical ability tests, contextual problem-solving assignments, and interview guidelines. The results of the cognitive style test (MFFT) were analyzed by calculating the time spent working on and the correct answers, the results of the mathematics ability test were analyzed according to the scoring guidelines, and the task of solving contextual problems was analyzed according to the indicators of the thinking process in solving the problems that had been created. The results of the study show that 1) Reflective students carry out the stages of solving problems properly and thoroughly without making mistakes until they find the final answer to the problem given. 2) Impulsive students experience mistakes and are not careful in solving the problem because they cannot find answers to the problems given.